50 success classics winning wisdom for work & life from 50 landmark books - Butler-Bowdon, Tom (Nicholas Brealey Pub., 2004)
We are all seeking answers to how to achieve life success. In "50 Success Classics" Tom Butler-Bowdon goes back to basics, to find the classic books on staying true to ourselves and fulfilling our potential.